Micropropagation and assessment of genetic stability of Dendrobium transparens Wall. Ex Lindl. using RAPD and ISSR markers - Joshi, Pusp Raj; Pandey, Sushma; Maharjan, Lasta; Pant, Bijaya (Frontiers in Conservation Science, 2023)
Abstract An efficient in vitro propagation protocol for Dendrobium transparens was established using seed derived protocorms, and the genetic homogeneity of the in vitro regenerants and the wild plant was also investigated. Full Murashige and Skoog mediums produced the most seed germination (FMS). On both basal and half-strength MS medium, protocorms were induced. The most shoots (11.9 shoots/explant) were obtained in half MS medium fortified with 100 mL/L coconut water, as well as 1 mg/L Benzyl amino purine (BAP) and 2 mg/L Kinetin. Elongated shoots were then transferred to full and half strength MS root initiating medium supplemented with various auxin concentrations. However, in full MS medium fortified with 100 mL/L coconut water and 1.5 mg/L Napthalene acetic acid, a maximum of (8.3 ± 0.6, 4.9 ± 0.1 cm) roots were obtained (NAA). To examine genetic stability among in vitro and mother plants, ten RAPD and ISSR primers were used. RAPD primers generated 23 fragments, while ISSR primers generated 16 fragments. The amplified bands of all in vitro plant samples were similar to the bands of the mother plant. The current study shows that tissue culture can be used for true-to-type plant production and conservation of D. transperens.